2015
DOI: 10.1142/s0219633615500273
|View full text |Cite
|
Sign up to set email alerts
|

The effect of anchoring groups on the electro-optical and charge injection in triphenylamine derivatives@Ti6O12

Abstract: The triphenylamine (TPA), thiophene and pyrimidine are being used as e±cient advanced functional semiconductor materials. In the present study, some new TPA donor--acceptor derivatives were designed where TPA moiety acts as donor, thiophene-pyrimidine -bridge and acetic/cyanoacetic acid as acceptor. The ground-state geometries were optimized at B3LYP/6-31G** level of theory. The excitation energies and oscillator strengths were computed at TD-CAM-B3LYP/6-31G** (polarizable continuum model (PCM), in methanol) l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 61 publications
(58 reference statements)
0
6
0
Order By: Relevance
“…Recently, we have optimized the geometries of organic compounds different compounds by using B3LYP functional and proved that it is reliable approach to reproduce the experimental data [8,[14][15][16][17][18][19]. The absorption wavelengths have been computed by using TD-DFT [20,21].…”
Section: Computational Detailsmentioning
confidence: 99%
“…Recently, we have optimized the geometries of organic compounds different compounds by using B3LYP functional and proved that it is reliable approach to reproduce the experimental data [8,[14][15][16][17][18][19]. The absorption wavelengths have been computed by using TD-DFT [20,21].…”
Section: Computational Detailsmentioning
confidence: 99%
“…Geometry optimization was performed by using hybrid DFT/B3LYP functional within C2 symmetry constrain and subsequent TD-DFT calculation at the optimized geometry was performed for the first 70 vertical singlet excitations [31,33,34]. Double zeta 6-31G(d,p) basis set was used for geometry optimization while flexible LANL2DZ basis set was used for TD-DFT calculation [35][36][37]. Molecular orbital (MO) contributions of each transition were analyzed using Gaussian version 2.2 software package [38].…”
Section: Computational Protocolmentioning
confidence: 99%
“…All calculations were performed by using density functional theory (DFT) [16][17][18] in Gaussian 09 software [19]. Previously, it has been shown that B3LYP is a good and rational functional [20][21][22][23][24][25]. The B3LYP/6-31G*, B3LYP/6-31G**, B3LYP/6-31+G* and B3LYP/6-31+G** levels of theory has been applied to optimize the ground state geometries and to calculate the harmonic vibrational frequencies (for both parent (ArOH) systems and radicals (ArO .…”
Section: Computational Detailsmentioning
confidence: 99%